Outcomes of Neonates Born To Mothers Who Were COVID-19 Positive; An Observational Study from Pakistan - Ahmad, Zeeshan; Khushdil, Arshad; Waqar, Talal; Ahmed, Madiha; Haque, Khalid N; Sultana, Rashida; Sughra, Umme e; Farooq, Shoaib; Malik, Qudrat Ullah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess outcomes of neonates born to mothers who were COVID-19 positive.Study Design: Prospective observational study.Place and Duration of Study: Secondary and Tertiary Care Hospitals of the Armed Forces, Pakistan, from Apr to Aug 2020.Methodology: We studied 106 pregnant women who tested positive for SARS-CoV-2. Stable asymptomatic newborn babies were kept in SARS-CoV-2 specified incubators, at specially designated areas for observation. Nasopharyngeal swabs were taken at first 24 hours and if negative, babies were handed over to clinically stable mothers who were educated regarding use of facemasks and proper hand washing. Neonates who tested positive for SARS-CoV-2 were evaluated for SARS-CoV-2 again at 48 hours and then every 48-72 hours, until found to be negative.Results: Total 106 women were found to be SARS-CoV-2 positive during the study period. All the women delivered singleton babies. Of the 106 babies, 5 (4.71%) were found to be positive for SARS-CoV-2 at 24 hours and only 1 (0.94%) baby was found to be positive at 48 hours and then tested negative at 7th day.Conclusion: Babies born to SARS-CoV-2 mothers were mostly asymptomatic and there was no increased risk of morbidity or mortality to the neonates suffering from the infection.